The Efficacy of Marmot Brown Fat in Treatment of Acute Pancreatitis - Dagdanbazar, Nyamdorj; Bodi, Dagdanbazar; Dorjkhuu, Amgalanbaatar; Shuumarjav, Uurtuya; Zunduin, Ariunaa; Lkhagvasuren, Munkhtulga; Sundui, Enebish (Central Asian Journal of Medical Sciences, 2016)
Objectives: The brown fat of marmots is called "human meat" among Mongolian people because they abstain from eating it. Our experimental study is the first academic-based study to investigate the effect of marmot brown fat (MBF) on acute pancreatitis (AP). Methods: This study used 82 healthy female Wistar rats (250-280 g). The study rats were divided into 4 groups: (1) relatively healthy (no medication and no AP, n = 10), (2) caerulein-induced AP rats without any treatments (n = 24), (3) AP rats fed by the MBF suspension (n = 24), and (4) AP rats injected with sandostatin (n = 24). The serum a-amylase level (SAAL) and histological examination were observed. Results: Significantly increased SAAL (group 1: 1347.10 ±10.76 units/L vs group 2: 1804.50 ±134.32 units/L) was confirmed in rats with caerulein-induced, mild AP. In both treatment groups 3 and 4, the SAAL was significantly decreased on the fifth day after treatment. Interestingly, advanced damage of pancreatic cells was observed in group 3. Additionally, the health condition of group 3 rats was poor, and spleen and lung tissue damage was detected by histological examination. Conclusion: Our study results suggest that the MBF suspension might be stimulating pancreatic juice secretion, therefore we conclude that the MBF suspension is not beneficial in the treatment of AP.